Regional Disparities in Measles Vaccination Coverage and Their Associated Factors: An Ecological Study in Japan - Masaki Machida; Shinji Fukushima; Takahiro Tabuchi; Tomoki Nakaya; Wakaba Fukushima; Shigeru Inoue (Journal of Epidemiology)
Background: The decline in measles vaccination coverage is a global concern. In Japan, coverage of the first dose of measles vaccine, which had exceeded the target of 95.0% since fiscal year (FY) 2010, fell to 93.5% in FY 2021. Vaccination coverage increased to 95.4% in FY 2022 but varied by municipality. Few studies have focused on regional disparities in measles vaccination coverage. This study aimed to clarify the regional disparities in measles vaccination coverage by municipality in Japan and their associated factors. Methods: In this ecological study, the measles vaccination coverage in FY 2022; population density; area deprivation index (ADI; an indicator of socioeconomic status); proportion of foreign nationals, single-father households, single-mother households, and mothers aged ≥30 years; and number of medical facilities, pediatricians, and non-pediatric medical doctors in 1,698 municipalities were extracted from Japanese government statistics. Negative binomial regression was performed with the number of children vaccinated against measles as the dependent variable, number of children eligible for measles vaccination as the offset term, and other factors as independent variables. Results: Vaccination coverage was less than 95.0% in 54.3% of municipalities. Vaccination coverage was significantly positively associated with population density and negatively associated with the proportion of single-father households, mothers aged ≥30 years, and the ADI (incidence rate ratios: 1.004, 0.976, 0.999, and 0.970, respectively). Conclusion: This study showed regional disparities in measles vaccination coverage in Japan. Single-father households, age of mothers, and socioeconomic status may be key factors when municipalities consider strategies to improve vaccination coverage.